210k views
3 votes
What is one root of this equation 2x^2-4x+9=0?

A. -2+sqrt14/2i
B. -1+sqtr14/2i
C. 1+sqrt14/3i
D. 1+sqrt14/2i
E. 2+sqrt14/2i

2 Answers

1 vote

For this case we have the following quadratic equation:


2x ^ 2-4x + 9 = 0

The solutions are given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

We have to:


a = 2\\b = -4\\c = 9

Substituting:


x = \frac {- (- 4) \pm \sqrt {(- 4) ^ 2-4 (2) (9)}} {2 (2)}\\x = \frac {4 \pm \sqrt {16-72}} {4}\\x = \frac {4 \pm \sqrt {-56}} {4}\\x = \frac {4 \pm \sqrt {-1 * 56}} {4}\\x = \frac {4 \pmi \sqrt {2 ^ 2 * 14}} {4}\\x = \frac {4 \pm2i \sqrt {14}} {4}\\x = \frac {2 \pm i\sqrt {14}} {2}

Answer:


x_ {1} = \frac {2 + i \sqrt {14}} {2}\\x_ {2} = \frac {2-i \sqrt {14}} {2}

User Jeen Broekstra
by
5.5k points
3 votes

Answer:

OPTION E:
(2+√(14)i)/(2)

Explanation:

Given the Quadratic equation
2x^2-4x+9=0, you can find the roots by applying the Quadratic formula. This is:


x=(-b\±√(b^2-4ac) )/(2a)

In this case you can identify that:


a=2\\b=-4\\c=9

Then you can substitute values into the Quadratic formula:


x=(-(-4)\±√((-4)^2-4(2)(9)) )/(2(2))


x=(4\±√((56) )/(4)

Remember that
√(-1)=i, then:


x=(4\±2√(14)i)/(4)

Simplifying, you get:


x=(2(2\±i√(14)i))/(4)\\\\x=(2\±√(14)i)/(2)\\\\\\x_1=(2+√(14)i)/(2)\\\\x_2=(2-√(14)i)/(2)

User Erki Aring
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.